The Rwandan 1959 social revolution and its antecedents: The beginning of the genocide against Tutsi? - Evariste Erwin Sebahutu (Universitas PGRI Madiun, 2023)
The integrated-blame game theory of ethnicity explains how the current Rwandan ethnoscape evolves regardless of the so called de-ethnicization policy adopted by the current regime. Ethnocentrism blamed on the Hutu from the 1950s when they claimed their civic rights, has been the founding philosophy of the Tutsi Nyiginya dynasty and continues to be the corner stone for the current Tutsi dominated regime. Speeches and writings of contemporary political elites such as the one of Dr Jean Damascène Bizimana are part of the plan of politicization of biased history as a tool of legitimization of political exclusion currently practiced. Events that took place in 1957 and subsequent years did not happen in vacuum, their origins are traced back to the creation and expansion of the Tutsi Nyiginya dynasty and its power abuse records. While these events are part of steps taken mutually by both ethnic groups from oppressive kingship towards bloody revolution, after independence interethnic violence, war and genocide against the Tutsi, and subsequent massacres of Hutu civilians both in Rwanda and Congo and happened when both ethnic groups failed to compromise on their rivalries in the first place; they fulfill all the requirements both by definitions and theories to be called a “social revolution”.